Vulnerability assessment of araceous on climate change in Kinabalu UNESCO global geopark, Sabah, Malaysia - Rasyidah Wahab; Kartini Saibeh; Badariah Saibeh; Ejria Saleh (GEOGRAFIA Online, 2025)
Biodiversity has increasingly been challenged by environmental changes, particularly in protected areas where species are often endemic and sensitive to the environmental changes. Changes in this habitat expose organisms to vulnerability. Aracena, one of the most species-rich plant families, is widely distributed in the Kinabalu Geopark and is utilized by local communities for food, medicine, and ornamental purposes. However, its survival is increasingly threatened by climate related stressors and human activities. This study assesses the vulnerability of Aracena to social ecological activities across six study areas (Poring, Monggis, Serinsim, Nalapak, Sayap, and Losou Podi) using a modified Coastal Integrity Vulnerability Assessment Tool (CIVAT) and Social Ecological Resilience (SER) framework. The assessment incorporated three key components: exposure, sensitivity, and adaptive capacity. Results reveal that Losou Podi, Sayap, Monggis, and Nalapak exhibited low vulnerability, while Poring and Serinsim scored medium vulnerability due to pressures from tourism and illegal harvesting. These results highlight the effectiveness of current conservation measures within the park but also emphasize the need for targeted interventions in more vulnerable zones. Given these findings, this study provides a baseline for conservation strategies tailored to enhance Aracena resilience under climate stress.